Iconographies of rare causes of medullary compression due to primary vertebro-medullary and epidural hydatidosis: Contribution of imaging - Nourrelhouda Bahlouli; Kaouthar Imrani; Fatima Chait; Adam Sqalli houssaini; Sfar Kaouthar; Ihssane Lahlou; Moatassimbillah Nabil; Ittimad Nassar (Radiology Case Reports)
Vertebro-medullary and epidural hydatidosis are a very rare entity, representing 2% of all locations, and is even rarer when it involves a solitary location. It is often asymptomatic. The diagnosis is usually made during complications, particularly medullary compression or extension to the costal cage, which represents a therapeutic emergency. Surgical treatment must be radical to prevent recurrences. We report 2 cases: the first case was a 61-year-old female involved costo-vertebral hydatidosis, and the second was an 18-year-old man with primary sacral epidural location. The objective of our report is to add these 2 atypical locations of hydatid cysts to the existing literature and to present their radiological images to aid radiologists in diagnosis.